Genre analysis of experiment-based dental research article abstracts: Thai and international journals - Kriangkrai Vathanalaoha,; Supong Tangkiengsirisin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Academic dental abstracts play a pivotal role for readers to grasp the essence of scientific development in the world of dentistry as they particularly address on key information designated by dental researchers. However, the generic structures of Thai and international dental research article abstracts have not been investigated as a means of pedagogical implication in terms of English for Specific Purposes (ESP). This study aims to investigate generic structures of Thai and international dental research article abstracts and compare the results with respect to the linguistic features found within the two datasets. Two separate datasets of 120 abstracts were randomly selected and compiled from dental journals certified by Thai-Journal Citation Index (TCI) and Impact Factors (IF), respectively, were analysed by Kanoksilapatham’s (2013) BPMRD nomenclature of abstract analysis. A set of linguistic features based on Pho’s (2008) and Hyland’s (2004) frameworks also reported to show linguistic variation in dental research article abstracts between Thai and international writers. The data shows that Move B is apparently disregarded by Thai writers while the others are comparatively similar. Regarding linguistic features, objective writing is more emphasised by Thai writers through the omission of self-reference pronouns and the lack of modalities. As international publication is a milestone for professional success in higher education, the results from this study can stress on a means of developing writing pedagogy that can be globally used within the academic discourse of dentistry.